Extent of Adoption of Improved Cultivation Practices of Watermelon - Bhajipale, DD; Kharde, PB; Karangami, RS (Indian Journal of Extension Education, 2021)
Watermelon is an important vegetable crop grown in Solapur district as such present study was conducted in Solapur district of Maharashtra state. A total of 120 respondents from ten villages formed sample for the study. The data were obtained by interview schedule. It was observed that, 56.66 per cent of respondents had completely adopted harrowing, 52.50 per cent respondents had completely adopted rotavator for watermelon cultivation, 60.00 per cent of the watermelon growers had adopted normal recommended planting distance, 78.33 per cent of watermelon growers had completely adopted the recommended seed rate for sowing of watermelon, 74.17 per cent of the respondents had complete adoption of sugar baby variety of watermelon, 55.83 per cent of the respondents had complete adoption of recommended basal dose of fertilizers as per MPKV, Rahuri, 93.33 percent of the respondents had completely adopted the cultural methods for weed the recommendation of management, 31.67 per cent respondents had adopted the flood method of irrigation. In overall, nearly two third 65.00 per cent of watermelon growers had medium level of adoption.